A facile molecularly imprinted electrochemical sensor based on graphene: application to the selective determination of thiamethoxam in grain. Issue 62 (8th August 2017) - Xie, Tianjiao; Zhang, Min; Chen, Pan; Zhao, Haitian; Yang, Xin; Yao, Lei; Zhang, Hua; Dong, Aijun; Wang, Jing; Wang, Zhenyu
Abstract : In this study, we report a facile method for the preparation of molecularly imprinted polymer based graphene for the electrochemical detection of thiamethoxam residue. Abstract : In this study, we report a facile method for the preparation of molecularly imprinted polymer based graphene for the electrochemical detection of thiamethoxam residue. We choose p -vinylbenzoic acid as a functional monomer; it can be used to add recognition units and alkenyl units onto the surface of graphene via π–π interactions in just one step, effectively simplifying the reaction process. And an ultra-thin imprinting film (2 nm) is formed by reducing the addition step involving the alkenyl modifier. Due to the irreversible electrochemical reduction characteristics of thiamethoxam, the template can be removed easily using cyclic voltammetry scanning, without the need for organic solvents. The performance of the fabricated sensor was evaluated and the results indicated that the sensor exhibited excellent specific recognition abilities for thiamethoxam detection; the imprinting factor is 2.36. The peak current from thiamethoxam is linearly proportional to its concentration over the range from 0.5 to 20 μM, and the detection limit is 0.04 μM. The practical application of the sensor was also realized in the selective detection of thiamethoxam in real samples.